2019
DOI: 10.1504/ijrapidm.2019.10017666
|View full text |Cite
|
Sign up to set email alerts
|

A study on machinability evaluation of Al-Gr-B<SUB align="right">4C MMC using response surface methodology-based desirability analysis and artificial neural network technique

Abstract: In this work, machinability behaviour of aluminium-graphite-boron carbide metal matrix composite is performed during wire-cut electrical discharge machining (WEDM) process. Experiments were designed using central composite-face centred design of response surface methodology (RSM) and with the application of desirability function multiple quality characteristics viz., kerf width, surface roughness and material removal rate (MRR) were optimised simultaneously. Input parameters gap voltage, pulse ON-time, pulse O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…such as machining polarity, peak current, pulse duration, among others, on the wire-cut electrical discharge machining (WEDM) characteristics such as material removal rate, surface roughness [12] and [13]. Tsoukalas [14] and Hsu and Do [15] used an L 27 orthogonal array of Taguchi method to determine the optimum conditions leading to minimum porosity in aluminium alloy die castings.…”
Section: Cutting Forces and Surface Roughness In Face-milling Of Skd6mentioning
confidence: 99%
“…such as machining polarity, peak current, pulse duration, among others, on the wire-cut electrical discharge machining (WEDM) characteristics such as material removal rate, surface roughness [12] and [13]. Tsoukalas [14] and Hsu and Do [15] used an L 27 orthogonal array of Taguchi method to determine the optimum conditions leading to minimum porosity in aluminium alloy die castings.…”
Section: Cutting Forces and Surface Roughness In Face-milling Of Skd6mentioning
confidence: 99%
“…The significance of the model formulated was verified with the help of Analysis of variance (ANOVA) technique as well as response surface model fitting [16,17]. ANOVA for final Ra and MRR are given in Table 4 and 5 respectively.…”
Section: Design Of Experiments and Observationsmentioning
confidence: 99%
“…From the evaluated results they have concluded that Al6061 aluminum series shows good drilling performance when compared with the other series. 15 From the literature survey, it was concluded that there was a lack of study on influence of hot extrusion process on the mechanical and machinability of the composites. In this experimental work, various weight proportions of B 4 C ceramic particles were added into the Al6061 alloy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…From the evaluated results they have concluded that Al6061 aluminum series shows good drilling performance when compared with the other series. 15…”
Section: Introductionmentioning
confidence: 99%